International conference on policy and institutional options for the management of rangelands in dry areas. Workshop summary paper - Ngaido, T.; McCarthy, N.; Gregorio, M. di (CGIAR System Organization, 2002)
The System-wide Program for Collective Action and Property Rights (CAPRI) sponsored an International Conference on Policy and Institutional Options for the Management of Rangelands in Dry Areas, May 7-11, 2001 in Hammamet, Tunisia. The conference focused on institutional aspects of rangeland management and brought together policy makers and researchers from North Africa, Sub-Saharan Africa and West Asia to discuss sustainable rangeland production strategies and livelihood of pastoral communities in dry areas. This conference summary paper contains summaries of the CAPRI sponsored research findings on institutional options for rangeland, policy makers' interventions and reactions as well as the synthesis of discussion groups. These working groups evaluated outcomes of policies and institutions guiding rangeland management in terms of their impact on livelihoods and environmental sustainability, and explored alternative policies and institutional strategies in light of their capacity to reduce poverty and enhance food security.